Review on Liposome Based Cancer Theragnostics and Therapy - Current Advancements - Maiyazhaganaar Logendiran; Hariny Rajeswary Radhakrishnan; Krishnanand Nagarajan; Latha Subbiah; Selvamani Palanisamy (International Journal of Pharma and Bio Sciences, 2020)
Liposomes are well-established biocompatible nanocarrier systems widely used for site-directed and controlled drug delivery applications. Unique properties of liposomes such as biocompatibility, biodegradability, controllable size, low immunogenicity, and low toxicity offer a great promise for their use as drug carriers in drug delivery applications for treatment of a variety of diseases. The purpose of this review is to provide an overview on the state-of-the-art of theragnostic applications of liposomes reported so far in brief. The drug loaded liposome formulations enable controlled diffusion of drugs within plasma leading in improved biodistribution and pharmacokinetics of drugs. Liposomes by virtue of its architecture are capable of delivering both hydrophilic and hydrophobic drugs at the site of action. The efficiency of liposomes to encapsulate various therapeutic and diagnostic agents together had resulted in significant interest in the use of liposomes for theragnostic applications. In this brief review, we had presented the lipid based drug delivery carrier systems, liposomes and its variants designed and developed for theragnostic applications with special reference to cancer therapy. We also highlighted the novel drug delivery aspects using liposomes and current advancements in multifunctional liposomes in cancer imaging, diagnostic and therapy. There is great potential for expanded role for liposomes in the clinic and further efforts to this end is warranted. To conclude, this mini review will provide an insight to the students and researchers who work in the field of nanotheragnostics.